GEOMORPHOLOGY AND SEDIMENTOLOGY OF UNION GLACIER AREA, ELLSWORTH MOUNTAINS, OCCIDENTAL ANTARCTICA - do Couto Silva Costa, Vanessa; Vieira, Rosemary; Cardia Simões, Jefferson (Revista Brasileira de Geomorfologia, 2017)
The work aims to investigate the geomorphological and sedimentological aspects of Union Glacier area (79°45’00’’S; 82°30’00’’W), southern sector of Ellsworth Mountains. Geomorphological cartography based on 15 m ASTER (2010) satellite imagery and field works were carried out during the Brazilian expedition (2011/2012) enabled the identification of morainic formations: ice-cored hummock moraines, supraglacial moraines, and recession moraines in the interior of the valleys. With the exception of the latter one, all types of moraines have been developed on the blue-ice areas. The evidence for paleo wet-based glacial conditions is reconstructed from a range of geomorphological record, including exposed abrasion marks, striations and glaciotectonic deformation. This type of deformation is represented by lee sides of oversteepening bedrock promontories which follow the tributaries of glaciers ice flow. Glacial sediments were collected from the moraines for granulometric and morphometric analyses. They show the prevalence of sandy gravel and sand texture, low quantity of fine fractions, and absence of attributes such as striated and faceted clasts, which indicate, on the other side, low-sediment transport capacity from the ice sheet bottom. It is inferred that the moraine debris are originated from local sources. Weathering action and constant katabatic winds are possibly the major agents of transport and alteration of the exposed sediments. The geomorphological features reveal an ancient thicker ice sheet, and sedimentary characteristics of the morainic formations reveal a latter thinner ice sheet in this sector of Ellsworth Mountains.